HONORING THE VOICES OF YOUTH IN OUT-OF-HOME CARE: INSIGHTS INTO RESTRICTIONS DURING THE COVID-19 PANDEMIC, AND FUTURE PERSPECTIVES - Equit, Claudia; Thomas, Elisabeth (International Journal of Child, Youth and Family Studies, 2025)
Recent studies focusing on children and youth in care have emphasized the increased challenges that emerged with the restrictions related to the COVID-19 pandemic. There is, however, not enough comprehensive research on how caregivers could have systematically improved the social participation of young people in care. Here we present initial results based on the qualitative part of a joint project, entitled “JuPa”, which focuses on the social participation of young people during and after the COVID-19 pandemic in Germany. Due to the relevance of young people’s voices in research and practice, the project includes participatory methods to involve youth in care systematically. In the qualitative part of JuPa, 40 interviews with youth in care were analyzed. Pandemic-related effects on youth in care, their coping strategies, and their concepts for the future are emphasized. The youth were optimistic about the future despite the impact the COVID-19 pandemic had had on their lives. The described challenges make clear the necessity of implementing youth-friendly children’s rights.